Psychopathology and abnormal psychology - Davey, Graham (Sage benchmarks in Psychology, 2015)
This major work provides a structured and comprehensive insight into the areas of psychopathology and abnormal psychology - topics that cover the causes and treatments of mental health problems. This is a notably interdisciplinary field that intersects a number of domains of psychological science including clinical psychology, child psychology, experimental psychology, social psychology and neuropsychology, as well as touching upon other areas of study, such as education. It also forms the knowledge base for professions such as clinical psychology and psychiatry. This collection's contents are structured thematically and each of the five volumes is dedicated to an important area of psychopathology or abnormal psychology. Additionally, each volume includes an introduction written by the work's acclaimed editor, Graham C. Davey, which maps out the volume's structure and highlights the significance of each article and the how the subject matter in that area has developed.